2017
DOI: 10.3389/fevo.2017.00077
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Contributions of Cardinals Are Consistent with a Hypothesis of Relaxed Selection in Urban Landscapes

Abstract: Human activities are leading to rapid environmental change globally and may affect the eco-evolutionary dynamics of species inhabiting human-dominated landscapes. Theory suggests that increases in environmental heterogeneity should promote variation in reproductive performance among individuals. At the same time, we know that novel environments, such as our urbanizing study system, may represent more benign or predictable environments due to resource subsidies and ecological changes. We tested the hypothesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Alternatively, by favouring adaptive phenotypes that provide a fitness advantage, both directional and stabilizing selection can deplete phenotypic variation in a population over time, via a reduction of the underlying genetic variance across generations or the selective disappearance of certain individuals within each generation. However, relaxed selection may be more pervasive in cities than previously thought (e.g., [13], including in humans [20]). A recent meta-analysis found that anthropogenic disturbances in nonurban habitats reduce the strength of selection [21].…”
Section: Selectionmentioning
confidence: 93%
See 2 more Smart Citations
“…Alternatively, by favouring adaptive phenotypes that provide a fitness advantage, both directional and stabilizing selection can deplete phenotypic variation in a population over time, via a reduction of the underlying genetic variance across generations or the selective disappearance of certain individuals within each generation. However, relaxed selection may be more pervasive in cities than previously thought (e.g., [13], including in humans [20]). A recent meta-analysis found that anthropogenic disturbances in nonurban habitats reduce the strength of selection [21].…”
Section: Selectionmentioning
confidence: 93%
“…However, we still know little about how urbanization shapes phenotypic variation, the target of selection that will determine the ecology and future evolution of urban populations. Few studies have compared phenotypic variation between urban and non-urban populations [5,6,15,[7][8][9][10][11][12][13][14](Table S1) and, to our knowledge, no studies have directly examined the causal mechanisms and consequences of this variation.…”
Section: Urban Phenotypic Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows animals to access a more predictable environment typical of urban settings, where they may be able to nd more abundant resources and subsidies (Martínez-Abraín and Jiménez 2016;Rodewald and Arcese 2017).…”
Section: Introductionmentioning
confidence: 99%